Determinants of the downward sloping segment of the EKC in high-income countries: The role of income inequality and institutional arrangement - Hyangsuk Cho (Cogent Economics & Finance, 2021)
Even among developed countries, each country has very different circumstances and political institutions regarding environmental issues. Moreover, the differences in individual attitudes about environmental issues within national borders and in the types of environmental behaviors affect the environmental policy of each country. Therefore, in contrast to the Environmental Kuznets curve (EKC) hypothesis, the effect of economic growth on environmental degradation differs between high-income countries. Evidences show that economic growth is not the only determinant of environmental change, particularly in high-income countries. In this respect, this paper examines the existence of the EKC as well as the effects of the level of political institution on the relationship between greenhouse gas (GHG) emission per capita and income inequality; it does this by using unbalanced data for 33 OECD countries from 1990 to 2014. The findings of this study show that the level of income inequality differentially affects the GHG emission depending on the level of institution. The EKC hypothesis holds only in countries with a high level of institution, and the threshold of the EKC is positioned at a lower income level in countries with stronger institutional arrangement, and such countries also show lower GHG emission per capita.
Keywords: 330; Environmental degradation; environmental Kuznets curve; environmental tax; greenhouse gas emission; income inequality; political institution